2007
DOI: 10.1007/s10620-006-9579-1
|View full text |Cite
|
Sign up to set email alerts
|

Reasons Why Patients Infected with Chronic Hepatitis C Virus Choose to Defer Treatment: Do They Alter Their Decision with Time?

Abstract: This study was designed to determine the percentage of treatment-naïve patients infected with chronic hepatitis C virus who make an informed choice to forego (defer) treatment with pegylated interferon regimens in the absence of any medical, psychosocial, or other contraindications, and to reassess their decision by using a questionnaire at least 1 year later. Patient charts dating from 2001 were retrieved and retrospectively analyzed for the following data: patient age, gender, race, hepatitis C viral load, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 59 publications
(73 reference statements)
3
38
1
Order By: Relevance
“…Increased efforts should be made to encourage HCV treatment in appropriate patients in effort to decrease morbidity and mortality related to the disease. efficacy as well as the concern over side effects of interferon and ribavirin [1,3]. Both of our medical center populations behaved similarly in this regard, and we suspect similar rates exist in other large urban centers.…”
Section: To the Editormentioning
confidence: 57%
See 2 more Smart Citations
“…Increased efforts should be made to encourage HCV treatment in appropriate patients in effort to decrease morbidity and mortality related to the disease. efficacy as well as the concern over side effects of interferon and ribavirin [1,3]. Both of our medical center populations behaved similarly in this regard, and we suspect similar rates exist in other large urban centers.…”
Section: To the Editormentioning
confidence: 57%
“…[1], which revealed that of 280 treatment-naïve patients with chronic hepatitis C who had no contraindication to receiving interferon-based therapy, 115 patients declined therapy. African American patients were more likely than non-African American patients to decline treatment.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…The retrospective nature of our study did not allow us to further investigate socioeconomic and insurance status of these patients. Of note, a previous study showed that patients who decided not to undertake treatment at the initial setting were unlikely to change their decisions over time, as most patients believed they remained asymptomatic [29]. It signified the importance of the assessment and counseling together with provision of financial assistance to HCV-infected patients by an experienced multidisciplinary team at the initial setting.…”
Section: Discussionmentioning
confidence: 99%
“…4,[16][17][18][19] Not surprisingly, a general fear and apprehension regarding side effects and their impact on quality of life and functioning are common among patients considering treatment. [20][21][22] Despite these side effects and related patient concerns, some recommend early treatment for coinfected patients to prevent more serious disease development. 23 Several psychosocial factors may also contribute to a patient's treatment decisions.…”
mentioning
confidence: 99%